2019
DOI: 10.3390/su11236636
|View full text |Cite
|
Sign up to set email alerts
|

On the Asymmetries of Sovereign Credit Rating Announcements and Financial Market Development in the European Region

Abstract: In modeling the impact of sovereign credit rating (CR) on financial markets, a considerable amount of the literature to date has been devoted to examining the short-term impact of CR on financial markets via an event-study methodology. The argument has been established that financial markets are sensitive to CR announcements, and market reactions to such announcements (both upgrading and degrading) are not the same. Using the framework of an autoregressive distributed lag setting, the present study attempted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 56 publications
0
27
1
2
Order By: Relevance
“…This indicates that changes in explanatory variables reflect the different effects of independent variables. This study assesses the EKC hypothesis and the implications of the asymmetric impacts of GDP_PC absorptive capacity on CO 2 emissions in the USA and China using the nonlinear autoregressive distributed lag (NARDL) model which is prominent in recent studies [67,68]. Considering the factors' nature and economic growth, and global policies towards the CO 2 emissions-environment policy nexus, the study adopts a nonlinear framework.…”
Section: Empirical Approachmentioning
confidence: 99%
“…This indicates that changes in explanatory variables reflect the different effects of independent variables. This study assesses the EKC hypothesis and the implications of the asymmetric impacts of GDP_PC absorptive capacity on CO 2 emissions in the USA and China using the nonlinear autoregressive distributed lag (NARDL) model which is prominent in recent studies [67,68]. Considering the factors' nature and economic growth, and global policies towards the CO 2 emissions-environment policy nexus, the study adopts a nonlinear framework.…”
Section: Empirical Approachmentioning
confidence: 99%
“…There have been numerous surveys on impacting factors of innovation strategy choice, especially centering on corporate governance, including ownership structure [4], the board of directors structure [5], executive incentive [6], and manager characteristics [7,8]. In addition, the financial market has an important influence on the sustainability of developing countries [9]; Sun and Zhang [10] find that the improvement of financial development level can maintain the sustainability of enterprise operations by promoting exploratory innovation. The contemporary research has assisted in clarifying the affecting factors and mechanisms of innovation strategy choice but overlooked the influence of the institutional environment on innovation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…As one would expect, municipal debt was significantly impacted by the debt crisis. Also affected, via economic and social variables, was the accounting principle of going concerned, i.e., the sustainability of financial management and the simultaneous risk of default (Cohen et al, 2017;Li et al, 2019;Khan et al, 2020) The factors influencing municipal debt in several European countries (Austria, Belgium, France, Germany, Italy, and Spain) were studied by Bellot and Martí Silva (2017). They concluded that the countries in question shared features in common in the practices of their local and central governments.…”
Section: Literature Reviewmentioning
confidence: 99%